Analisis Lapisan Batuan dan Potensi Air Tanah dengan Metode Geolistrik Konfigurasi Schlumberger di Kampus 2 UIN Sunan Gunung Djati Bandung - Agustina, Rena Denya; Pazha, Haekal; Chusni, Muhammad Minan (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
Geoelectric is the method most often used to obtain subsurface images with the possibility of groundwater and minerals at a certain depth. Estimations by means of this method are based on the fact that different materials will have different types of resistance when electrified. The purpose of this research is to estimate the electrical properties of subsurface rock formations, especially their ability to generate electricity or inhibit electricity. The results showed that the tested area had soil geological conditions which were dominated by soil, sand and gravel in the surface area, whereas for 50 m depth it was dominated by sedimentary rocks accompanied by basalt rocks with little saline in the deepest layer. For large resistivity in the range of 3000 - 5000 Wm it indicates that the area has poor groundwater potential.